2006
DOI: 10.1007/s00418-006-0191-4
|View full text |Cite
|
Sign up to set email alerts
|

Prospero-related homeobox 1 (Prox1) is a stable hepatocyte marker during liver development, injury and regeneration, and is absent from “oval cells”

Abstract: The aim of this study was to analyse the changes of Prospero-related homeobox 1 (Prox1) gene expression in rat liver under different experimental conditions of liver injury, regeneration and acute phase reaction, and to correlate it with that of markers for hepatoblasts, hepatocytes, cholangiocytes and oval cells. Gene expression was studied at RNA level by RT-PCR, and at protein level by immunohistochemistry. At embryonal stage of rat liver development (embryonal days (ED) 14-16) hepatoblasts were found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 31 publications
2
42
0
Order By: Relevance
“…Other markers of the progenitor compartment-such as Cldn3, Ncam1, Dlk1, and Onecut2-are enriched in the YFP + population only at day 14, indicating that previously reported markers can be classified to early markers and later markers (Schmelzer et al 2006;Snykers et al 2009;Tanaka et al 2009). In addition, YFP + cells were enriched for cholangiocyte markers Ck19 (Krt19), Ck7 (Krt7), Onecut1, and Hnf1b, as well as hepatocyte markers Hnf4a, Hnf1a, and Prox1 (Dudas et al 2006;data not shown (Seymour et al 2007).…”
Section: Foxl1-crementioning
confidence: 99%
“…Other markers of the progenitor compartment-such as Cldn3, Ncam1, Dlk1, and Onecut2-are enriched in the YFP + population only at day 14, indicating that previously reported markers can be classified to early markers and later markers (Schmelzer et al 2006;Snykers et al 2009;Tanaka et al 2009). In addition, YFP + cells were enriched for cholangiocyte markers Ck19 (Krt19), Ck7 (Krt7), Onecut1, and Hnf1b, as well as hepatocyte markers Hnf4a, Hnf1a, and Prox1 (Dudas et al 2006;data not shown (Seymour et al 2007).…”
Section: Foxl1-crementioning
confidence: 99%
“…Despite a high protein sequence similarity between Prospero and Prox1, the amino acid motif responsible for this asymmetric segregation of Prospero seems not present in Prox1 , and asymmetric segregation of Prox1 has not been reported to date. Like Prospero, Prox1 is also expressed in many other organs, such as the liver, brain, pancreas, heart, eye lens, ear sensory epithelium, taste bud, and retina (Oliver et al 1993;SosaPineda et al 2000;Govindarajan and Overbeek 2001;Miura et al 2003;Bermingham-McDonogh et al 2006;Dudas et al 2006;Edqvist et al 2006;Laerm et al 2007;Kirjavainen et al 2008;Risebro et al 2009). Interestingly, the cell-fate-specifying function of Prospero seems to have been inherited by Prox1 and appears to be the common functional theme of Prox1 in such diverse cell types.…”
Section: Prox1: the Master Regulator For Lymphatic Developmentmentioning
confidence: 99%
“…Ubiquitin C expression was not aVected by any of the treatments used in the animal models. The normalized Thy-1, Fibulin-2, Desmin, Gremlin and SMA PCR-product quantities of treated animals were compared to the values of control animals, and the relative expression was plotted against the observation time ( Dudas et al 2006Dudas et al , 2007. In all cases, two or more animal series were analyzed in duplicates.…”
Section: Rna Isolation and Real-time Rt-pcrmentioning
confidence: 99%